Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13046-020-01551-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interplay between linc01134 and YY1 dictates hepatocellular carcinoma progression

Abstract: Background: Revealing the mechanical role of long non-coding RNAs (lncRNAs) in tumorigenesis can contribute to novel therapeutic target for cancers. The regulatory role of linc01134 in hepatocellular carcinoma (HCC) has not been studied yet. Materials and methods: qRT-PCR and western blot were conducted to measure relevant RNA and protein expressions. CCK-8, colony formation, EdU, flow cytometry, wound-healing, transwell assays and xenograft experiments were performed to determine the role of linc01134 in HCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Among these lncRNAs, RHPN1-AS1 was reported to act as an oncogene in multiple human cancers, including nonsmall cell lung cancer [19], uveal melanoma [20], and breast cancer [21]. LINC01134 and MKLN1-AS were found to promote HCC progression or metastasis by previous studies [24][25][26][27][28], suggesting that the two lncRNAs might be more specific in HCC, while NRAV and CMB9-22P13.1 were 13 BioMed Research International rarely reported as an oncogene in cancers. Similar with RHPN1-AS1, MAPKAPK5-AS1 was frequently reported to act as tumor-promoting lncRNAs in multiple cancers like thyroid cancer, colorectal cancer, glioma, lung cancer, and HCC [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Through regulating NF-κB signaling, the effects of LINC01134 and AKT1S1 on HCC cell proliferation and apoptosis need further investigation. During our revision, another group reported that LINC01134 promotes EMT and metastasis of HCC through the LINC01134/miR-324-5p/IGF3BP1/YY1 axis (Rong et al, 2020). We both reported the pro-metastatic roles of LINC01134 in HCC.…”
Section: Discussionmentioning
confidence: 65%
“…10 While miR-134-5p overexpression has been confirmed to be capable of reducing SGC7901 cells' proliferation, colony formation and invasion. 11 All these studies verify the value of miRNAs in regulating GC progression. As an ubiquitous transcription factor, Yin Yang 1 (YY1) can drive tumorigenesis, metastasis and drug resistance, and targeting YY1 is deemed to be a potential therapeutic option for various malignant tumors.…”
Section: Introductionmentioning
confidence: 62%